Daily field checking list by Walter Rosene, May 3, 1933 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated May 3, 1933. This checklist was used by Walter Rosene to record birds sighted around Adix and Crawford Ponds, and North Bridge with Bob Walker between 6:00 and 9:00. Plustek--flatbed